Solving the Equation (x+1)(x3) = 0
This equation is a simple quadratic equation in factored form. To solve for the values of x that satisfy the equation, we can use the Zero Product Property.
Zero Product Property
The Zero Product Property states that if the product of two or more factors is equal to zero, then at least one of the factors must be equal to zero.
Applying the Property
In our equation, (x+1) and (x3) are the factors. Therefore, to find the solutions, we set each factor equal to zero and solve:

x + 1 = 0 Subtracting 1 from both sides, we get: x = 1

x  3 = 0 Adding 3 to both sides, we get: x = 3
Solution
Therefore, the solutions to the equation (x+1)(x3) = 0 are x = 1 and x = 3. These values of x make the equation true because when substituted into the original equation, they result in a product of zero.